2015
DOI: 10.1136/bmjopen-2014-007473
|View full text |Cite
|
Sign up to set email alerts
|

Lung protective ventilation in patients undergoing major surgery: a systematic review incorporating a Bayesian approach

Abstract: ObjectiveProtective ventilation (PV) has been validated in patients with acute respiratory distress syndrome. However, the effect of PV in patients undergoing major surgery is controversial. The study aimed to explore the beneficial effect of PV on patients undergoing a major operation by systematic review and meta-analysis.SettingVarious levels of medical centres.ParticipantsPatients undergoing general anaesthesia.InterventionsPV with low tidal volume.Primary and secondary outcome measuresStudy end points inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…8 mL/kg predicted bodyweight). This is in line with current recommendations [25][26][27] and is used in previous clinical trials of intraoperative ventilation before [12,13,15], allowing for good comparison of the DESIGNATION results with those from preceding trials.…”
Section: Discussionsupporting
confidence: 77%
“…8 mL/kg predicted bodyweight). This is in line with current recommendations [25][26][27] and is used in previous clinical trials of intraoperative ventilation before [12,13,15], allowing for good comparison of the DESIGNATION results with those from preceding trials.…”
Section: Discussionsupporting
confidence: 77%
“…Zhang et al 39 performed a systematic review of 22 studies of subjects undergoing general anesthesia during major surgery and the development of ALI. They found that lower V T ventilation was associated with a protective effect against the development of ALI.…”
Section: Ventilation Of Surgical Patientsmentioning
confidence: 99%
“…These adverse effects of NIV could be avoided by using IMV. For example, protective ventilation strategy can be performed with IMV [25,26], but it is impossible under NIV. Furthermore, the use of NIV or HFNC can delay IMV, leading to emergency or more unstable intubations [27].…”
Section: Discussionmentioning
confidence: 99%